Strategic Marketing in the Development of the Tourism Economy: Meleura Beach - La Ode Andi Hermawan; Usman Rianse; Wade Rahma Batin; Muhammad Suriyadarman Rianse; Ahmad Ridwan; Sarman Sarman; La Ode Muhammad Misran Jumadi Suha (International Journal of Tourism and Hospitality in Asia Pasific, 2025)
Tourism plays a significant role in the economic development of Indonesia, particularly in areas like Meleura Beach, Muna Regency, Southeast Sulawesi, which offers unique natural landscapes and cultural heritage. However, local MSMEs in the region face challenges in promoting their products and services due to limited digital marketing skills and technological adaptation. This study aims to explore the role of strategic marketing, especially digital marketing, in enhancing the attractiveness of the Meleura Beach tourism destination. A qualitative research approach, combining SWOT analysis and FGDs, was employed to assess the current marketing strategies of MSMEs and their potential for growth. The findings revealed that while businesses possess strengths in their unique products and local resources, many face weaknesses such as insufficient digital marketing capabilities and infrastructure. Opportunities for growth lie in leveraging digital marketing tools and community-based tourism, but threats from competition and regulatory changes remain significant. The study concludes that enhancing digital literacy among MSMEs, supported by government and private sector collaboration, is essential for increasing market reach and competitiveness. It is recommended that MSMEs focus on digital marketing, community involvement, and partnerships with international agencies to ensure long-term growth and sustainability in the global tourism market.